Ab initio molecular dynamics simulation of the structural and electronic properties of aluminoborosilicate glass. Issue 7 (17th March 2021) - Gong, Haiming; Song, Bin; Yang, Yuting; Wang, Peixian; Cao, Zhiqiang; Chen, Xiaojie; Zhao, Gaoling; Peng, Shou; Liu, Yong; Han, Gaorong
Abstract: In this study, the structural and electronic properties of aluminoborosilicate glass, which has a wide range of applications in fields such as microelectronics and displays, were examined using ab initio molecular dynamic simulations. Computing models containing 220 atoms correctly described the local structure of the glass. The reliability of the computing models was verified by the consistency between the experimental results, obtained using high‐energy X‐ray diffraction and solid‐state nuclear magnetic resonance, and the simulation results pertaining to structural factors, pair distribution functions, Q n distribution, and elastic properties. The presence of B and Al increased the flexibility and asymmetry of the system, as shown by the bond angle and ring size distributions. Based on the electronic properties, we observed that the introduction of Al and B atoms into the network could also cause covalent interactions with the O atoms, similar to that with Si atoms. However, the Na and Mg atoms still interacted with all kinds of atoms in the network via charge transfer and exhibited highly non‐localized effects on the charge of the network formers. These results extend our understanding of the structure of aluminoborosilicate glass and have guiding significance for improving and designing new types of this glass.